Nitrogen-doped hollow mesoporous carbon nanosheets and their preparation method and application in potassium ion batteries

Through the preparation of nitrogen-doped hollow mesoporous carbon nanosheets, the problems of low mass specific capacity of carbon-based materials and large changes in electrode volume in potassium ion batteries are solved, and potassium ion batteries with high-quality specific capacity and cycle stability are achieved, which is significantly Improves the electrochemical performance of the battery.

CN115498194BActive Publication Date: 2025-01-10XIAMEN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211219283.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-30
Publication Date
2025-01-10
Estimated Expiration
2042-09-30

AI Technical Summary

Technical Problem

The mass specific capacity of carbon-based materials in potassium ion batteries is lower and the electrode volume changes greatly during the battery cycle, resulting in material damage and battery failure.

Method used

Using nitrogen-doped hollow mesoporous carbon nanosheets as the negative electrode material of potassium ion battery, prepared by monodispersed silica nanosheets as templates, resorcinol-formaldehyde resin coating and high-temperature calcination and etching to form a high specific surface area and mesoporous carbon nanosheets, providing abundant potassium ion intercalation sites and buffering volume changes.

Benefits of technology

It improves the mass specific capacity and cycling stability of potassium ion batteries, reduces the effective current density of the electrode, significantly improves the diffusion coefficient and migration rate of potassium ions, and extends the battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115498194B_ABST
    Figure CN115498194B_ABST
Patent Text Reader

Abstract

Nitrogen-doped hollow mesoporous carbon nanosheets and their preparation methods and applications in potassium ion batteries, the nitrogen-doped hollow mesoporous carbon nanosheets include a carbon shell and a reduced graphene oxide wrapped therein; the carbon shell is covered with mesopores vertically connecting the inner and outer walls. The preparation method is as follows: tetrapropoxysilane is subjected to a hydrolysis and polycondensation reaction in a graphene solution to obtain a silicon dioxide nanosheet template, resorcinol and formaldehyde are used as carbon source precursors, ammonia water is used as an alkaline catalyst and a nitrogen source, and tetrapropoxysilane is used as a pore-forming agent to carry out a resorcinol-formaldehyde resin coating reaction, the product is subjected to high-temperature calcination, and finally etching is performed to remove the silicon dioxide nanosheets. The nitrogen-doped hollow mesoporous carbon nanosheets provide a considerable mass specific capacity and exhibit excellent rate performance and cycle stability, and can be used as an ideal carbon-based current collector material for potassium ion negative electrodes, and then used to construct safe, high mass specific capacity and long cycle life potassium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of potassium ion battery electrode materials, and in particular to nitrogen-doped hollow mesoporous carbon nanosheets and a preparation method thereof and application in potassium ion batteries. Background Art

[0002] Lithium-ion batteries have become a necessity in our lives, but people's demand for energy has grown rapidly with the development of science and technology. The mineral resources of lithium and cobalt, the main electrode materials of commercial lithium-ion batteries, are scarce in the earth's crust and are extremely unevenly distributed, which greatly increases the production cost of lithium-ion batteries. The content of potassium in the earth's crust is two orders of magnitude higher than that of lithium. And the Stokes radius of potassium ions in propylene carbonate, a common electrolyte solvent, is Smaller than lithium-ion This means that potassium ions have better diffusion kinetics than lithium ions, which is manifested in a larger diffusion coefficient and a higher diffusion rate. Although the voltage of the potassium ion electrode relative to the standard hydrogen electrode is -2.93V, which is slightly higher than the -3.04V of the lithium ion electrode relative to the standard hydrogen electrode, the cyclic voltammetry test in the electrolyte system shows that the potassium metal deposition potential is about 0.1V lower than the lithium metal deposition potential, which means that potassium ion batteries can achieve a higher operating voltage range, which also means that potassium ion batteries with higher energy density can be achieved.

[0003] Compared with lithium ions, potassium ions have many advantages in electrolyte systems. Currently, many different types of materials are regarded as highly promising negative electrode materials for potassium ion batteries. Among them, carbon-based materials are regarded as one of the ideal negative electrodes for potassium ion batteries due to their low cost, simple preparation process and excellent mechanical properties. However, limited by the large ionic radius of potassium ions and their corresponding insertion and extraction mechanisms, the mass specific capacity of carbon-based materials is not high. And when the battery is cycled, the electrode will produce a large volume change, resulting in damage to the electrode material and battery failure. Summary of the invention

[0004] The object of the present invention is to solve the above-mentioned problems in the prior art, and to provide nitrogen-doped hollow mesoporous carbon nanosheets and their preparation methods and applications in potassium ion batteries. Using monodispersed silica nanosheets as templates, resorcinol-formaldehyde resin as carbon source, ammonia water as alkaline catalyst and nitrogen source, and tetrapropoxysilane as pore-forming agent, after surface coating of silica nanosheets, heat treatment carbonization, and hydrofluoric acid etching, the resulting product is a nitrogen-doped hollow mesoporous carbon nanosheet with a large cavity. Among them, the carbon nanosheet has a very large specific surface area and can provide abundant potassium ion embedding sites, so that a higher mass specific capacity can be obtained. The mesopores distributed on the carbon nanosheet shell can not only increase the specific surface area of ​​the carbon nanosheet, but also buffer the volume change caused by the potassium ion de-embedding at the active site. After multiple cycles of the potassium ion de-embedding process, the carbon nanosheet itself remains stable.

[0005] In order to achieve the above object, the present invention adopts the following technical scheme:

[0006] The present invention provides a nitrogen-doped hollow mesoporous carbon nanosheet, wherein the nitrogen-doped hollow mesoporous carbon nanosheet comprises a carbon shell and reduced graphene oxide in a hollow inner cavity of the carbon shell, and the carbon shell is formed by nitrogen-doped mesoporous amorphous carbon.

[0007] Furthermore, the specific surface area of ​​the carbon shell is 1300-1450m 2 / g.

[0008] Furthermore, the nitrogen atom doping amount of the carbon shell is 2.5 mol% to 4 mol%.

[0009] Furthermore, the thickness of the carbon shell is 30-60 nm.

[0010] Furthermore, the carbon shell is full of mesopores vertically connecting the inner and outer walls, and the pore size of the mesopores is concentrated in the range of 6 to 9 nm. Through transmission electron microscopy observation, it can be seen that the nitrogen element is evenly distributed in the carbon nanosheets, which means that a large number of evenly distributed active sites can be provided for potassium ion deintercalation, providing a considerable mass specific capacity.

[0011] The present invention also provides a method for preparing nitrogen-doped hollow mesoporous carbon nanosheets, which comprises the following steps:

[0012] S1, uniformly dispersing graphene oxide in a reaction system, and then allowing tetrapropoxysilane to undergo a hydrolysis and polycondensation reaction under alkaline conditions so as to coat the surface of the graphene oxide to obtain monodisperse silica nanosheets coated with graphene oxide;

[0013] S2, using the silica nanosheet obtained in S1 as a template, resorcinol and formaldehyde as carbon source precursors, the remaining ammonia water in the reaction in step S1 as an alkaline catalyst and a nitrogen source, and the remaining tetrapropoxysilane in the reaction in step S1 as a pore-forming agent to carry out a resorcinol-formaldehyde resin coating reaction to obtain a silica nanosheet with a surface coated with resorcinol-formaldehyde resin;

[0014] S3, calcining the silica nanosheets coated with resorcinol-formaldehyde resin at high temperature to carbonize the resorcinol-formaldehyde resin contained therein, and then etching the high-temperature calcined product to remove the template silica nanosheets to obtain nitrogen-doped hollow mesoporous carbon nanosheets.

[0015] Furthermore, in step S1, the method for dispersing graphene oxide is to add the graphene oxide powder to a mixed solution of ethanol, water and ammonia water, and then ultrasonically disperse it to obtain a monodisperse graphene oxide suspension; the method for the hydrolysis and polycondensation reaction is to add the tetrapropoxysilane to the above suspension, and then stir the reaction in a water bath at 20 to 40°C for 5 to 20 minutes to obtain a monodisperse silica nanosheet suspension.

[0016] Furthermore, relative to 1 mg of the graphene oxide, the amount of ethanol used is 10 to 30 mL, the amount of deionized water used is 1 to 2 mL, the amount of ammonia water used is 0.5 to 1 mL, and the amount of tetrapropoxysilane used is 0.5 to 1 mL.

[0017] Furthermore, in step S2, the method of the resorcinol-formaldehyde resin coating reaction is to add resorcinol and formaldehyde in the monodisperse silica nanosheet suspension in sequence, react with magnetic stirring for 20 to 30 hours, centrifuge and wash, and dry to obtain silica nanosheets with the surface coated with resorcinol-formaldehyde resin.

[0018] Furthermore, relative to the mentioned 1 mg of graphene oxide, the amount of resorcinol used is 20-50 mg, and the amount of formaldehyde used is 0.4-0.7 mL.

[0019] Furthermore, in step S3, the high-temperature calcination is carried out by grinding the silica nanosheets coated with resorcinol-formaldehyde resin on the surface (the grinding degree is sufficient as long as the agglomerated particles can be dispersed), and then heating the ground product to 700-900°C at a rate of 1-5°C / h under the protection of inert gas or nitrogen and keeping the temperature for reaction for 2-6h. After the reaction is completed, it is cooled to room temperature to obtain a high-temperature calcined product.

[0020] Furthermore, in step S3, the etching method is to dissolve the high-temperature calcined product in a hydrofluoric acid solution with a concentration of 5wt% to 15wt%, magnetically stir the reaction for 8 to 15 hours, then separate the solid and liquid and centrifuge the obtained solid to wash it (for example, by three centrifugation washes with deionized water / deionized water / ethanol), and dry it to obtain nitrogen-doped hollow mesoporous carbon nanosheets.

[0021] The present invention also provides the use of the nitrogen-doped hollow mesoporous carbon nanosheet as a carbon nanosheet current collector material for a potassium ion negative electrode.

[0022] In addition, the present invention also provides a potassium ion battery, which includes a potassium ion negative electrode, wherein the potassium ion negative electrode uses the nitrogen-doped hollow mesoporous carbon nanosheet as a current collector material.

[0023] The nitrogen-doped hollow mesoporous carbon nanosheets prepared by the method provided by the present invention can provide abundant potassium ion active sites and limit the volume change during the potassium ion extraction / insertion process, and can be used as an ideal carbon-based current collector material for potassium ion negative electrode, and then used to construct a safe, high-quality specific capacity and long-life potassium ion battery. In addition, the preparation process of the nitrogen-doped hollow mesoporous carbon nanosheets provided by the present invention is simple, the material cost is low, and it is expected to become a potassium ion battery negative electrode current collector material with excellent electrochemical performance and commercial potential.

[0024] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0025] (1) The nitrogen-doped hollow mesoporous carbon nanosheets provided by the present invention have a mesoporous hollow structure, a high specific surface area (1300-1450 m 2 / g), macropore volume (1.8~2.3cm 3 / g), which can effectively promote the transmission of ions / electrons and reduce the effective current density of the electrode;

[0026] (2) The nitrogen atom doping amount of the nitrogen-doped hollow mesoporous carbon nanosheets provided by the present invention is 2.5 mol% to 4 mol%, wherein the nitrogen atoms exist in the form of pyrrolic nitrogen (prN) and pyridinic nitrogen (pdN), respectively, and a small amount of O atoms are also present. The presence of N atoms and O atoms can significantly improve the affinity between amorphous carbon and potassium ions, promote the desorption / embedding behavior of potassium ions in amorphous carbon, thereby obtaining a higher mass specific capacity and a stable coulombic efficiency;

[0027] (3) The nitrogen-doped hollow mesoporous carbon nanosheets provided by the present invention have a large hollow inner cavity structure, and the carbon shell is covered with mesoporous channels with a diameter of 6 to 9 nm that vertically connect the inner and outer walls, which not only greatly increases the specific surface area of ​​the material and improves the wettability of the electrolyte on the electrode material, but also accelerates the migration rate of potassium ions in the electrolyte and increases the diffusion coefficient of potassium ions through capillary action;

[0028] (4) The carbon shell thickness of the nitrogen-doped hollow mesoporous carbon nanosheets provided by the present invention is 30 to 60 nm. Thanks to the superior mechanical properties of amorphous carbon, the volume change during the potassium ion extraction / embedding process can be effectively buffered. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 A flow chart of preparing nitrogen-doped hollow mesoporous carbon nanosheets according to the present invention;

[0030] Figure 2 The morphology characterization pictures of the nitrogen-doped hollow mesoporous carbon nanosheets obtained in Example 1, wherein a is a SEM picture, b is a TEM picture, and c is a high-resolution TEM picture;

[0031] Figure 3 The dark field photographs and element distribution diagrams of the nitrogen-doped hollow mesoporous carbon nanosheets obtained in Example 1, wherein a is a HADDF photograph, b is a C element distribution diagram, c is an O element distribution diagram, and d is a N element distribution diagram;

[0032] Figure 4 The XPS spectrum of the nitrogen-doped hollow mesoporous carbon nanosheets obtained in Example 1, a is the full spectrum, b is the N1s fine spectrum;

[0033] Figure 5 The nitrogen adsorption-desorption curve (a) and pore size distribution diagram (b) of the nitrogen-doped hollow mesoporous carbon nanosheet obtained in Example 1 and the nitrogen adsorption-desorption curve (c) and pore size distribution diagram (d) of the nitrogen-doped hollow microporous carbon nanosheet obtained in Comparative Example 1;

[0034] Figure 6 Cyclic voltammograms at different scan rates obtained when the nitrogen-doped hollow mesoporous carbon nanosheet obtained in Example 1 is used as a potassium ion negative electrode and the pseudocapacitance contribution ratio calculated therefrom;

[0035] Figure 7 The constant current intermittent titration technology spectrum measured when the nitrogen-doped hollow mesoporous carbon nanosheet obtained in Example 1 and the nitrogen-doped hollow microporous carbon nanosheet obtained in Comparative Example 1 are used as potassium ion negative electrodes respectively;

[0036] Figure 8 The morphology characterization diagrams of the nitrogen-doped hollow microporous carbon nanosheets obtained in Comparative Example 1, wherein a is a SEM image, b is a TEM image, and c is a high-resolution TEM image;

[0037] Fig. 9 The electrochemical performance diagram of the nitrogen-doped hollow mesoporous carbon nanosheet obtained in Example 1 and the nitrogen-doped hollow microporous carbon nanosheet obtained in Comparative Example 1 as potassium ion negative electrode, wherein a is the current density of 0.1Ag -1 b is the mass specific capacity and Coulomb efficiency of the cycle at different current densities, c is the current density 2Ag -1 Mass specific capacity and coulombic efficiency of the lower cycle. DETAILED DESCRIPTION

[0038] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer and more understandable, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0039] Example 1

[0040] This example is used to illustrate the preparation method of nitrogen-doped hollow mesoporous carbon nanosheets provided by the present invention. Figure 1 As shown:

[0041] S1. 10 mg of graphene oxide powder was evenly dispersed in a mixed solution of 70 mL of ethanol, 10 mL of deionized water and 3 mL of ammonia water (mass fraction of 25%, the same below), and then 3.5 mL of tetrapropoxysilane was added. The mixture was reacted with magnetic stirring in a 30°C water bath for 15 min to obtain monodisperse silica nanosheets coated with graphene oxide.

[0042] S2. Add 0.4 g of resorcinol and 0.56 mL of formaldehyde aqueous solution (mass fraction of 36%, the same below) to the above solution, react with magnetic stirring in a 30°C water bath for 25 hours, centrifuge, and then wash the resulting solid three times with deionized water / ethanol by centrifugation. Collect the sample and dry it in an oven at 60°C for 12 hours to obtain silica nanosheets SiO2&resin@SiO2 coated with resorcinol-formaldehyde resin on the surface.

[0043] S3. Grind the silica nanosheets SiO2&resin@SiO2 coated with resorcinol-formaldehyde resin on the surface and put them into an alumina crucible, place them in a tubular furnace, use N2 as the gas source, heat the temperature to 800°C at a heating rate of 2°C / h, and keep it warm for 4 hours. After the reaction is completed, cool it to room temperature to obtain a high-temperature calcined product. Collect the high-temperature calcined product and disperse it in a 15wt% hydrofluoric acid (HF) aqueous solution. Magnetic stirring is used to react for 12 hours, and centrifugation is performed. Then the obtained solid is washed with deionized water / ethanol and finally dried to obtain nitrogen-doped hollow mesoporous carbon nanosheets, which are recorded as N-HMCNS.

[0044] The morphology characterization results of the nitrogen-doped hollow mesoporous carbon nanosheets N-HMCNS are shown in Figure 2As shown, a is a SEM image, b is a TEM image, and c is a high-resolution TEM image. Figure 2 The results in a~c show that the nitrogen-doped hollow mesoporous carbon nanosheet N-HMCNS includes a carbon shell and a hollow inner cavity. The thickness of the carbon shell is 50nm. From the scanning and transmission photos, it can be seen that the carbon shell is covered with densely distributed mesoporous channels that vertically connect the inner and outer walls, and the channel diameter is 6~9nm.

[0045] The HADDF images and element distribution of the nitrogen-doped hollow mesoporous carbon nanosheets N-HMCNS are shown in Figure 3 As shown, a is the HADDF photo, b is the C element distribution map, c is the O element distribution map, and d is the N element distribution map. Figure 3 The results show that C, N, and O elements are uniformly distributed in the nitrogen-doped hollow mesoporous carbon nanosheets N-HMCNS.

[0046] The XPS spectrum of the nitrogen-doped hollow mesoporous carbon nanosheet N-HMCNS is as follows Figure 4 As shown in the figure, a is the full spectrum of the sample, b is the N1s fine scanning spectrum, and its fitting results show the following peaks: pyridinic nitrogen (pnN, 397.6eV) and pyrrolic nitrogen (prN, 400.1eV). Figure 4 As can be seen from a and b, the carbon shell of the nitrogen-doped hollow mesoporous carbon nanosheet N-HMCNS is formed by nitrogen-doped mesoporous amorphous carbon, the nitrogen atom doping amount is 3.2 mol%, and pyrrolic nitrogen is the main component.

[0047] The nitrogen adsorption-desorption curves and pore size distribution of the nitrogen-doped hollow mesoporous carbon nanosheets N-HMCNS are shown in Figure 2. Figure 5 As shown in a and b, a is the nitrogen adsorption and desorption curve, and b is the pore size distribution diagram. Figure 5 -a It can be seen that the nitrogen adsorption-desorption curve of the nitrogen-doped hollow mesoporous carbon nanosheet N-HMCNS presents a typical IV-type curve characteristic, indicating that capillary condensation occurs during adsorption. Figure 5 -b It can be seen that the pore size of the nitrogen-doped hollow mesoporous carbon nanosheet N-HMCNS is mainly distributed in the range of 6 to 9 nm. According to calculations, the specific surface area of ​​the nitrogen-doped hollow mesoporous carbon nanosheet N-HMCNS is 1433.15 m 2 / g, pore volume is 2.03cm 3 / g, proving that it has an extremely high specific surface area and rich pore structure.

[0048] The cyclic voltammetry test results of the half-cell assembled with the nitrogen-doped hollow mesoporous carbon nanosheet N-HMCNS as the potassium ion negative electrode are shown in Figure 6 As shown in Figure 1, a is the voltage-current curve at different scan rates, and b is the pseudocapacitance contribution graph at different scan rates. Figure 6-a It can be seen that the nitrogen-doped hollow mesoporous carbon nanosheet N-HMCNS has good cycle stability. Figure 6 -a It can be seen that the pseudocapacitance contribution of the nitrogen-doped hollow mesoporous carbon nanosheet N-HMCNS is dominant during the cycle process. The extremely large specific surface area of ​​the nitrogen-doped hollow mesoporous carbon nanosheet N-HMCNS can provide abundant potassium ion adsorption sites to obtain a larger specific capacity.

[0049] The results of the constant current intermittent titration test of the half-cell assembled with the nitrogen-doped hollow mesoporous carbon nanosheet N-HMCNS as the potassium ion negative electrode are as follows Figure 7 As shown, a is the specific capacity-voltage curve during charge / discharge, and b is the voltage-diffusion coefficient curve during charge / discharge calculated based on the above. Figure 7 It can be seen from a and b that the nitrogen-doped hollow mesoporous carbon nanosheet N-HMCNS has a larger diffusion coefficient during charge / discharge, that is, it exhibits a higher potassium ion diffusion rate.

[0050] Example 2

[0051] This example is used to illustrate the preparation method of nitrogen-doped hollow mesoporous carbon nanosheets provided by the present invention. Figure 1 As shown:

[0052] S1. 10 mg of graphene oxide powder was evenly dispersed in a mixed solution of 70 mL of ethanol, 10 mL of deionized water and 2.5 mL of ammonia water (mass fraction of 25%, the same below), and then 3 mL of tetrapropoxysilane was added. The mixture was reacted with magnetic stirring in a 30°C water bath for 15 min to obtain monodisperse silica nanosheets coated with graphene oxide.

[0053] S2. Add 0.3 g of resorcinol and 0.42 mL of formaldehyde aqueous solution (mass fraction of 36%, the same below) to the above solution, react with magnetic stirring in a 30°C water bath for 20 hours, centrifuge, and then wash the resulting solid three times with deionized water / ethanol by centrifugation. Collect the sample and dry it in an oven at 60°C for 12 hours to obtain silica nanosheets SiO2&resin@SiO2 coated with resorcinol-formaldehyde resin on the surface.

[0054] S3. Grind the silica nanosheets SiO2&resin@SiO2 coated with resorcinol-formaldehyde resin on the surface and put them into an alumina crucible, place them in a tubular furnace, use N2 as the gas source, heat the temperature to 900°C at a heating rate of 2°C / h, and keep it warm for 4 hours. After the reaction is completed, cool it to room temperature to obtain a high-temperature calcined product. Collect the high-temperature calcined product and disperse it in a 15wt% hydrofluoric acid (HF) aqueous solution. Magnetic stirring is used to react for 12 hours, and centrifugation is performed. Then the obtained solid is washed with deionized water / ethanol and finally dried to obtain nitrogen-doped hollow mesoporous carbon nanosheets, which are recorded as N-HMCNS.

[0055] The nitrogen-doped hollow mesoporous carbon nanosheet N-HMCNS includes a carbon shell and a hollow cavity. The thickness of the carbon shell is 35nm. The carbon shell is covered with densely distributed mesoporous channels that vertically connect the inner and outer walls. The channel diameter is 6-9nm, and the nitrogen atom doping amount is 2.8mol%. The specific surface area is 1232.42m 2 / g, pore volume is 1.70cm 3 / g.

[0056] Example 3

[0057] This example is used to illustrate the preparation method of nitrogen-doped hollow mesoporous carbon nanosheets provided by the present invention. Figure 1 As shown:

[0058] S1. 15 mg of graphene oxide powder was evenly dispersed in a mixed solution of 70 mL of ethanol, 10 mL of deionized water and 4 mL of ammonia water (mass fraction of 25%, the same below), and then 5 mL of tetrapropoxysilane was added. The mixture was reacted with magnetic stirring in a 40°C water bath for 15 min to obtain monodisperse silica nanosheets coated with graphene oxide.

[0059] S2. Add 0.5 g of resorcinol and 0.7 mL of formaldehyde aqueous solution (mass fraction of 36%, the same below) to the above solution, react with magnetic stirring in a 40°C water bath for 30 hours, centrifuge, and then wash the resulting solid three times with deionized water / ethanol by centrifugation. Collect the sample and dry it in an oven at 60°C for 12 hours to obtain silica nanosheets SiO2&resin@SiO2 coated with resorcinol-formaldehyde resin on the surface.

[0060] S3. Grind the silica nanosheets SiO2&resin@SiO2 coated with resorcinol-formaldehyde resin on the surface and put them into an alumina crucible, place them in a tubular furnace, use N2 as the gas source, heat the temperature to 900°C at a heating rate of 2°C / h, and keep it warm for 2 hours. After the reaction is completed, cool it to room temperature to obtain a high-temperature calcined product. Collect the high-temperature calcined product and disperse it in a 15wt% hydrofluoric acid (HF) aqueous solution. Magnetic stirring is used to react for 12 hours, and centrifugation is performed. Then the obtained solid is washed with deionized water / ethanol and finally dried to obtain nitrogen-doped hollow mesoporous carbon nanosheets, which are recorded as N-HMCNS.

[0061] The nitrogen-doped hollow mesoporous carbon nanosheet N-HMCNS includes a carbon shell and a hollow cavity. The thickness of the carbon shell is 40nm. The carbon shell is covered with densely distributed mesoporous channels that vertically connect the inner and outer walls. The channel diameter is 6-9nm, and the nitrogen atom doping amount is 3.3mol%. The specific surface area is 1432.42m 2 / g, pore volume is 1.92cm 3 / g.

[0062] Comparative Example 1

[0063] Nitrogen-doped hollow microporous carbon nanosheets were prepared according to the method of Example 1, except that in steps S1 and S2, tetrapropoxysilane was replaced by tetraethoxysilane (the amount of tetraethoxysilane was the same as that in Example 1), and the rest was the same as that in Example 1 to obtain nitrogen-doped hollow microporous carbon nanosheets, which were recorded as N-HPCNS.

[0064] The morphology characterization results of the nitrogen-doped hollow microporous carbon nanosheets N-HPCNS are shown in Figure 8 As shown, a is a SEM image, b is a TEM image, and c is a high-resolution TEM image. Figure 8 The results of a to c show that the nitrogen-doped hollow microporous carbon nanosheet N-HPCNS includes a carbon shell and a hollow cavity, and the thickness of the carbon shell is 50nm. However, unlike the nitrogen-doped hollow mesoporous carbon nanosheet N-HMCNS, which has a carbon shell with vertically connected inner and outer walls and densely distributed mesoporous channels, the carbon shell of the nitrogen-doped hollow microporous carbon nanosheet N-HPCNS is loose, and the channels are irregular, with a channel diameter of about 3nm or less.

[0065] The nitrogen adsorption-desorption curves and pore size distribution of the nitrogen-doped hollow microporous carbon nanosheets N-HPCNS are shown in Figure 5 As shown in c and d, c is the nitrogen adsorption and desorption curve, and d is the pore size distribution diagram. Figure 5 It can be seen that the specific surface area of ​​the nitrogen-doped hollow microporous carbon nanosheet N-HPCNS is 1046.20 m 2 / g, pore volume is 1.22cm 3 / g, and the pore size is mainly distributed below 3nm.

[0066] Test Case

[0067] The nitrogen-doped hollow mesoporous carbon nanosheets N-HMCNS obtained in Example 1 and the nitrogen-doped hollow microporous carbon nanosheets N-HPCNS obtained in Comparative Example 1 were respectively used as potassium ion negative electrodes to assemble half-cells to test their potassium ion diffusion coefficients and the potassium ion diffusion coefficients at 0.1 A g -1 , 2Ag -1 The long cycle performance at current density and rate performance at different current densities. Figure 7 and Fig. 9 As shown, Figure 7 -a is the voltage-specific capacity curve obtained by constant current intermittent titration technique, and 7-b is the potassium ion diffusion coefficient calculated based on this result. Fig. 9 -a is at a current density of 0.1A -1 9-b is the rate performance of the cycle at different current densities, and 9-c is the current density 2A. -1 The mass specific capacity and coulombic efficiency of the cycle under the condition of nitrogen-doped hollow mesoporous carbon nanosheets N-HMCNS were compared. According to the test results, the nitrogen-doped hollow mesoporous carbon nanosheets N-HMCNS showed better electrochemical performance than the nitrogen-doped hollow microporous carbon nanosheets N-HPCNS under different test conditions. Specifically, the half-cell assembled with the nitrogen-doped hollow mesoporous carbon nanosheets N-HMCNS as the potassium ion negative electrode has a larger potassium ion diffusion coefficient than the half-cell assembled with the nitrogen-doped hollow microporous carbon nanosheets N-HPCNS as the potassium ion negative electrode during both charging and discharging. And the half-cell assembled with the nitrogen-doped hollow mesoporous carbon nanosheets N-HMCNS as the potassium ion negative electrode has a larger potassium ion diffusion coefficient than the half-cell assembled with the nitrogen-doped hollow mesoporous carbon nanosheets N-HMCNS as the potassium ion negative electrode at a current density of 0.1Ag -1 Cycle 120 times and current density 2Ag -1 After 1000 cycles, the battery maintained 310mAh g -1 and 145mAh g -1 The mass specific capacity of the battery was 200 mAh g / cm2, and the coulombic efficiency was stable at about 100%. In contrast, the nitrogen-doped hollow microporous carbon nanosheet N-HPCNS as a potassium ion negative electrode only maintained 203 mAh g / cm2 after half-battery cycle. -1 and 116mAh g -1 After cycling at different current densities, the half-cell assembled with the nitrogen-doped hollow mesoporous carbon nanosheet N-HMCNS as the potassium ion negative electrode has a mass specific capacity of 4Ag. -1 The current density can reach 112 mAh g -1 The mass specific capacity was then increased again to 0.05Ag -1 When cycling at a current density of 365 mAh g -1In contrast, the nitrogen-doped hollow microporous carbon nanosheets N-HPCNS as the potassium ion anode assembled half-cell only obtained 56 mAh g after cycling at different current densities. -1 and 248mAh g -1 These results all indicate that nitrogen-doped hollow mesoporous carbon nanosheets N-HMCNS are ideal negative electrode materials for potassium ion batteries.

[0068] According to the characterization of various materials and the results of electrochemical tests, it is shown that the unique mesoporous channel design of the vertically connected inner and outer walls of the nitrogen-doped hollow mesoporous carbon nanosheet N-HMCNS obtained in the embodiment not only greatly increases the specific surface area of ​​the material, and works together with nitrogen doping to provide abundant potassium ion extraction / embedding sites, but also the capillary action of the channel enhances the wettability of the electrolyte, which can give full play to the advantages of the large specific surface area of ​​the material, and also improve the diffusion rate of potassium ions in the electrolyte, and finally obtain a larger mass specific capacity. At the same time, thanks to the excellent mechanical properties of carbon-based materials and the large pore size of the mesopores themselves, the volume expansion of the material during potassium ion extraction / embedding can be well buffered, so the nitrogen-doped hollow mesoporous carbon nanosheet N-HMCNS exhibits excellent cycle stability, and prevents the battery from failing due to the destruction of the active material.

[0069] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, replace and modify the above embodiments within the scope of the present invention without departing from the principles and intent of the present invention.

Claims

1. A method for preparing nitrogen-doped hollow mesoporous carbon nanosheets, characterized in that The following steps are involved: 1) Dispersing graphene oxide in a mixed solution of ethanol, deionized water and ammonia water, then adding tetrapropoxysilane and stirring the reaction in a water bath; 2) adding resorcinol and formaldehyde aqueous solution to the solution obtained in step 1), stirring for reaction in a water bath, and then centrifuging, washing, and drying; 3) calcining the product obtained in step 2), dispersing it into a hydrofluoric acid aqueous solution, stirring for reaction, and finally centrifuging, washing, and drying; In step 1), relative to 1 mg of the graphene oxide, the amount of ethanol used is 10-30 mL, the amount of deionized water used is 1-2 mL, the amount of ammonia water used is 0.2-0.8 mL, and the amount of tetrapropoxysilane used is 0.5-1 mL; In step 2), the amount of resorcinol used is 20-50 mg, and the amount of formaldehyde aqueous solution used is 0.4-0.7 mL relative to 1 mg of graphene oxide; In step 1) and step 2), the water bath temperature is 20-40°C; the stirring reaction time in step 1) is 5-20 minutes, and the stirring reaction time in step 2) is 20-30 hours; In step 3), the calcination is carried out in nitrogen or inert atmosphere, the temperature is raised to 700-900°C at a rate of 1-5°C / h and the temperature is kept for reaction for 2-6h; In step 3), the concentration of the hydrofluoric acid aqueous solution is 5 wt% to 15 wt%, and the stirring reaction time is 8 to 15 hours.

2. A nitrogen-doped hollow mesoporous carbon nanosheet, characterized in that: The nitrogen-doped hollow mesoporous carbon nanosheet is prepared by the preparation method described in claim 1, comprising a carbon shell, wherein the carbon shell has a hollow inner cavity, and reduced graphene oxide is wrapped in the hollow inner cavity; the carbon shell is composed of porous amorphous carbon doped with nitrogen, and the nitrogen atom doping amount is 2.5 mol% to 4 mol%; the carbon shell is covered with mesopores vertically connecting the inner and outer walls, and the pore size of the mesopores is 6 to 9 nm.

3. The nitrogen-doped hollow mesoporous carbon nanosheet according to claim 2, characterized in that: The specific surface area of ​​the carbon shell is 1300-1450m 2 / g, and the thickness of the carbon shell is 30-60nm.

4. The use of a nitrogen-doped hollow mesoporous carbon nanosheet as claimed in claim 2 or 3, characterized in that: The nitrogen-doped hollow mesoporous carbon nanosheet is used as a carbon nanosheet current collector material for a potassium ion negative electrode.

5. A potassium ion battery, comprising a potassium ion negative electrode, characterized in that: The potassium ion negative electrode uses the nitrogen-doped hollow mesoporous carbon nanosheets described in claim 2 or 3 as current collector material.

Citation Information

Patent Citations

  • Nitrogen-doped porous hollow carbon sphere and preparation method thereof, application of nitrogen-doped porous hollow carbon sphere, and lithium metal battery

    CN110148754A

  • Sandwich-shaped hollow spherical lithium ion battery anode material and preparation method thereof

    CN110600682A